2019
DOI: 10.1155/2019/3403548
|View full text |Cite
|
Sign up to set email alerts
|

Polymers for Regenerative Medicine Structures Made via Multiphoton 3D Lithography

Abstract: Multiphoton 3D lithography is becoming a tool of choice in a wide variety of fields. Regenerative medicine is one of them. Its true 3D structuring capabilities beyond diffraction can be exploited to produce structures with diverse functionality. Furthermore, these objects can be produced from unique materials allowing expanded performance. Here, we review current trends in this research area. We pay particular attention to the interplay between the technology and materials used. Thus, we extensively discuss un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 206 publications
(340 reference statements)
0
15
0
Order By: Relevance
“…In this case, structure fabrication is guided by a computer model in a layer-by-layer fashion, with high structural complexity [ 8 ]. Among these methods, laser direct writing via two-photons polymerization (LDW via TPP) offers the advantage of high spatial resolution i.e., below the diffraction limit, full reproducibility of the structures and the possibility to imprint any desired geometries [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, structure fabrication is guided by a computer model in a layer-by-layer fashion, with high structural complexity [ 8 ]. Among these methods, laser direct writing via two-photons polymerization (LDW via TPP) offers the advantage of high spatial resolution i.e., below the diffraction limit, full reproducibility of the structures and the possibility to imprint any desired geometries [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…LDW via TPP stands out from the current 3D printing techniques and relies on focusing a femtosecond laser beam in a photoreactive polymer, where it triggers a highly localized photomodification [ 10 ]. LDW via TPP has unique advantages among other printing technologies, such as spatial resolution below the diffraction limit, no limitations concerning the 3D architectures that can be obtained and high reproducibility of the 3D structures [ 7 , 8 , 9 , 10 ]. For tissue engineering, LDW via TPP provides the means to fabricate 3D structures that sustain the healing of damaged tissue [ 9 , 10 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also shown that structures can be produced on various functional substrates, like optical fibers or semiconductors [23,24]. Combined with an immense selection of suitable polymers [25][26][27], it shows huge flexibility and applicability. In the context of the lab-on-chip field, it was shown to be a tool capable of integrating features into channels before they are sealed [28] or even afterward [29].…”
Section: Introductionmentioning
confidence: 99%
“…Both synthetic polymers as well as biopolymers derived from natural sources are currently finding application in tissue engineering applications. [18][19][20] Biologically derived polymers such as polysaccharides, proteins, and nucleic acids, do have advantages in that they already contain similar biochemical components to those which cells experience in actual tissue. This leads to good biocompatibility and is associated with typically low inflammatory response being observed in vivo.…”
mentioning
confidence: 99%